STRATEGI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL DALAM MENCAPAI PELAYANAN PRIMA DI KABUPATEN BEKASI - Heriawan Abdullah Kunta; Rina Susanti Hartono (Governance, 2021)
This study aims to determine the "Strategy of the Department of Population and Civil Registration in Achieving Excellent Service in Bekasi Regency" which is marked by the presence of people who complain or complain about the service that is not yet excellent. This has the potential to become a barrier to achieving these goals. This study uses a qualitative method. The data collection technique is done by means of interviews (interviews) and distributing questionnaires (questionnaires). The instrument used was a Likert scale model questionnaire, with data analysis used was categorization analysis. The sample of this study was 125 people who came to the Bekasi district civil registration and occupation service. The results of the analysis show that: (1) Based on the level of excellent service, the research subjects at Disdukcapil Bekasi regency where the attitude aspect is 62% in the good category, the attention aspect is 50% in the good category, the action aspect is 51% in the good category (Ability) 45% is in the bad category, then the appearance (appearance) is 51% in the good category and 46% is in the good category. This is based on the results of a questionnaire given to 125 research subjects. (2) Based on the conclusion of the research results, there are still obstacles in the ability aspect (ability) 45% which are categorized as not good such as slow service, limited information on service procedures, less informative service and still lack of human resources to provide services. (3) Based on the existing obstacles, Disdukcapil designs strategies to achieve excellent service such as updating administrative information, disdukcapil issues E-SIAK and makes requests through WhatsApp and adds to service human resources provided with administrative training.